Model Strategi Tumbuh Dan Bertahan Pada Pengelolaan Baitul Maal Wat Tamwil (BMT) Di Kabupaten Tulungagung Dan Ponorogo - Lantip Susilowati (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2018)
BMT faces internal business challenges from managers. External challenges come from members, business competitors and economic conditions. BMTs face obstacles in managing business growth strategies and survival strategies. The focus of the problem in this study; 1) What is the growth strategy for the management of Baitul Maal wat Tamwil? 2) How do you survive the management of Baitul Maal wat Tamwil? 3) Are there obstacles faced in the effort to grow and survive the management of Baitul Maal wat Tamwil (BMT)? This study was examined with a qualitative and interpretive type approach. The results of this study: 1) The growth strategy of BMT management is done by maximizing network and employee functions, the product contains the value of core product benefits and improved benefits, spatial planning shows fast service, contains art, and member comfort, promotion is carried out in the form of external marketing, internal and interactive. 2). Defending strategies in BMT management: not adding employees when not increasing productivity, removing mudharabah time deposits, profit sharing according to sharia, BMT Dinar Amanu still applies a special rate of 1% for mudharabah deposits, Supervision is carried out with supervision of all employees, DPS BMT Dinar amanu function not maximal. 3) Constraints faced in efforts to grow and survive on BMT management include lack of competent Human Resources, ready to challenge, less agile and less agile and KUR fund competition.